Peluang Penyelesaian Sengketa Perdata Tentang Tanah Melalui Alternative Dispute Resolution Dengan Asas-Asas Hukum Perjanjian Di Dalamnya - Wiguna, Made Oka Cahyadi (Jurnal Hukum & Pembangunan, 2018)
The current developments, there are many land disputes that are vertical or horizontal. Issues concerning land affairs are often caused by salim claims over land rights. The intended land dispute is a civil dispute concerning the land. Achieving a win-win solution in the settlement of civil disputes over land is relatively difficult to materialize, if the settlement is resolved through a trial (litigation). The choice of law that can be chosen to obtain and realize a win-win solution in solving civil disputes over land is of course through alternative dispute resolution. By way of negotiation, mediation and conciliation. In the course of the settlement of civil disputes over land settled through alternative dispute resolution, the settlement can not ignore the applicable legal principles of the treaty, namely the principle of freedom of contract, the principle of good faith, the principle of consensualism, the principle of pacta sunt servanda and the principle of personality